PEMBELAJARAN RME (REALISTIC MATEMATICS EDUCATION) TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIK PADA SISWA SMP - Hidayat, Wahyu; Jayanti, Koentri; Nurismadanti, Ilfa Febriana; Ikhsanuddin Akbar, Muhammad Zulfikar; Pertiwi, Kholifia Ayuning; Rengganis, Pusparini (IKIP Siliwangi, 2019)
This research aims to look at the difference in the ability of mathematical creative thinking in students, through Realistic Mathematical Education learning or RME and through conventional learning. The research design used was an experiment, namely in the form of a test of the ability of creative thinking. The population in this study of Junior High School students throughout the country, namely in West Bandung Regency. Sample research VIII grade i.e. in one of the Junior High School in West Bandung chosen at random and selected class A (grade experiment) that uses learning Realistic Mathematics Education (RME) and class B (grade control) that uses regular or conventional learning. The research results showed that the p-value of 0.000 < critical limits. Thus, the ability of mathematical creative thinking of the students who got the learning with Realistic Mathematics Education better than the students who got conventional learning.